2015
DOI: 10.7554/elife.04263
|View full text |Cite
|
Sign up to set email alerts
|

miR-128 regulates neuronal migration, outgrowth and intrinsic excitability via the intellectual disability gene Phf6

Abstract: miR-128, a brain-enriched microRNA, has been implicated in the control of neurogenesis and synaptogenesis but its potential roles in intervening processes have not been addressed. We show that post-transcriptional mechanisms restrict miR-128 accumulation to post-mitotic neurons during mouse corticogenesis and in adult stem cell niches. Whereas premature miR-128 expression in progenitors for upper layer neurons leads to impaired neuronal migration and inappropriate branching, sponge-mediated inhibition results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 52 publications
(84 reference statements)
5
87
0
1
Order By: Relevance
“…Consistent with this prediction, expression of miR-128 by in utero electroporation in the mouse brain arrests the migration of cortical neurons in layers III and IV–VI (Franzoni et al, 2015), which phenocopies the migration defects observed upon PHF6 knockdown (Zhang et al, 2013). Importantly, expression of PHF6 reverses the miR-128-induced migration defects (Franzoni et al, 2015), suggesting that PHF6 operates downstream of miR-128 in the regulation of cortical migration. Whether miR-128 regulation of PHF6 expression influences other aspects of brain development remains to be explored.…”
Section: Mechanisms Of Phf6 Functionsupporting
confidence: 52%
See 2 more Smart Citations
“…Consistent with this prediction, expression of miR-128 by in utero electroporation in the mouse brain arrests the migration of cortical neurons in layers III and IV–VI (Franzoni et al, 2015), which phenocopies the migration defects observed upon PHF6 knockdown (Zhang et al, 2013). Importantly, expression of PHF6 reverses the miR-128-induced migration defects (Franzoni et al, 2015), suggesting that PHF6 operates downstream of miR-128 in the regulation of cortical migration. Whether miR-128 regulation of PHF6 expression influences other aspects of brain development remains to be explored.…”
Section: Mechanisms Of Phf6 Functionsupporting
confidence: 52%
“…Downregulation of PHF6 expression is correlated with an increase in the expression levels of miR-128, suggesting that miR-128 may regulate PHF6 expression during brain development. Consistent with this interpretation, expression of miR-128 in cortical neurons triggers the downregulation of PHF6, an effect that is mediated by miR-128 binding sites within the 3′UTR of PHF6 mRNA (Franzoni et al, 2015). A prediction of these results is that miR-128 might influence neuronal migration in the cerebral cortex.…”
Section: Mechanisms Of Phf6 Functionmentioning
confidence: 78%
See 1 more Smart Citation
“…MyoD Prevent difference of postnatal myogenic progenitors [125] miR-128 Phf6, Bmi-1, P70S6K1 Control of neurogenesis and synaptogenesis suppress tumor proliferation and self-renewal [102,126] miR-294…”
Section: Coup-tfii Lefty1 Lefty2mentioning
confidence: 99%
“…Moreover, of the last two decades, clinical trials of pharmacological therapeutics either failed to prove efficacy or provided only modest reductions in functional deficits [7][8][9]. Notwithstanding compelling efforts were made to stimulate growth of regenerative axons in experimental SCI models, very limited success had been achieved because of irreversible neuronal loss and glial scar formation [10,11].…”
Section: Introductionmentioning
confidence: 98%